Religious Literacy as a Mediator in the Ecosystem Model of Religious Moderation Towards Youth's Tolerance Attitudes - Pajarianto, Hadi; Pribadi, Imam; Yusuf, Muhammad; Sulaeman; Sari, Puspa; Liu, Ming Chou; Sari, Harmita (NAJAHA, 2025)
The essence of religious moderation lies in transforming the perspectives and attitudes of religious groups toward diversity, rather than moderating the religion itself. This study aims to pinpoint and explore how the ecosystem of religious moderation shapes youth tolerance through religious literacy. The research was conducted in three regions of Indonesia: the western, central, and eastern areas. A total of 350 informants were selected proportionally. Using a mixed-methods approach, the study embraced an exploratory sequential design that integrates qualitative and quantitative methods. Quantitative data were analyzed using Structural Equation Modeling, while qualitative data were examined thematically. The findings indicate that the Religious Moderation Ecosystem (X1)—which consists of six components: society, education, religion, politics, the state, and the media—significantly influences youth tolerance (Y). Another key finding indicates that religious literacy functions as a mediating variable (Z) between the ecosystem and youth tolerance. The significance of religious literacy as a mediator constitutes the study’s novelty, demonstrating its ability to link the religious moderation ecosystem with tolerant attitudes among young people. These results carry both theoretical and practical implications, highlighting substantial direct and interceded relationships among the ecosystem, religious literacy, and tolerance. Furthermore, religious literacy is capable of mediating all elements of the religious moderation ecosystem in shaping tolerance, marking it as a novel contribution compared to prior research. This study is limited by the restricted number of respondents, which does not fully represent all regions. Therefore, future studies are recommended to explore the ecosystem of religious moderation with a more proportionate distribution of regions, respondents, and informants.